7 Evaluation of a new point of care quantitative cube reader for salivary analysis in the english premier league soccer environment. (13th October 2015) - Dunbar, J; Jehanli, A; Hazell, G
Abstract : A Point of Care (POC) test for measurement of salivary antibody or cortisol concentrations, using a Lateral Flow Device (LFD), has given rapid feedback to coaches and support staff in Premier League soccer clubs within a matter of minutes from sample collection. This has been useful in assessing fatigue levels, immune status and readiness to train/compete and offers a considerable time advantage over standard laboratory methods. This current paper assesses a new POC reader, which is smaller, quicker and cheaper than the current model. A total of 48 saliva samples taken during routine monitoring of a cohort of English Premier League soccer players (23.5 ± 6.4 y) using IPRO OFC kits on two separate occasions for the measurement of cortisol on the standard IPRO LFD Reader and the new IPRO Cube reader. The following week 50 samples from the same cohort were measured for sIgA concentration with both IPRO readers. The cortisol LFD showed good agreement on both readers; r = 0.96 (95% CI 0.93–0.98) with typical error of estimate 1.18 nM (95% CI 0.98–1.48) and no difference between the mean values on each reader: LFD Reader 7.5 nM (range 2.73–23.5 nM) v Cube 7.1 nM (range 2.24–25.8). The sIgA LFD measured with the Cube reader showed good agreement with the standard LFD Reader; r = 0.98 (95% CI 0.96–0.99) with typical error of estimate 29.9 (95% CI 24.9–37.4) μg/mL and higher but not significant different mean values on the Cube: mean 215.6 ± 163.8 μg/mL (range 34.7–621.1 μg/mL) v LFD Reader mean 148.3 ± 142.1 (range 20.0–518.8 μg/mL). The new Cube POC device shows suitable validity for use in the sporting environment and represents savings in cost and analysis time in comparison to previous methods.